Topical ALA-Photodynamic Therapy Combined with Acne Debridement and Meticulous Nursing for the Treatment of Moderate–Severe Acne in Adolescent Patients - Ren R; Bao S; Qian W; Zhao H (Dove Medical Press, 2021)
Rongxin Ren, Shiwei Bao, Wenjiang Qian, Hongyi Zhao Department of Plastic Surgery, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People's Republic of ChinaCorrespondence: Hongyi Zhao Email zhaohongyi991@yeah.netObjective: The present study aims to explore the effect of acne debridement + meticulous nursing on 5-aminolevulinic acid photodynamic therapy (ALA-PDT) in adolescent patients with moderate-severe acne.Methods: A total of 60 adolescent patients with moderate-severe acne who were admitted to our plastic surgery outpatient clinic between January 2018 and January 2020 were selected as the subjects of the present retrospective study. The patients were divided into two groups: the observation group and the control group (n = 30, each). Patients in the control group were treated with standardized ALA-PDT and conventional nursing, while patients in the observation group were treated with ALA-PDT and acne debridement + meticulous nursing intervention. The treatment's therapeutic effect, adverse reaction incidence, and patient satisfaction 6 months after treatment were compared between the two groups.Results: The acne debridement + meticulous nursing effectiveness was 86.7% in the observation group and 60% in the control group, and the adverse reaction incidence was 20% in the observation group and 46.7% in the control group. There existed statistically significant differences in the above-stated indicators between the two groups (p < 0.05). The difference in the visual analogue scores (VASs) for pain, which were measured immediately after the operations, between the two groups was not statistically significant (p > 0.05); however, the respective VAS differences between the two groups at 30 min and 60 min after the operation were statistically significant (p < 0.05). There was a statistically significant difference in patient satisfaction between the two groups (p < 0.05).Conclusion: In adolescent patients with ALA-PDT-treated moderate-severe acne, the application of acne debridement + meticulous nursing could improve the clinical treatment efficacy and patient comfort as well as reduce the adverse reaction incidence. For these reasons, the treatment method could be worth promoting in clinical practice.Keywords: photodynamics, 5-aminolevulinic acid, psychology, pain, meticulous nursing, acne debridement